2017
DOI: 10.1088/1757-899x/279/1/012024
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-induced property improvement of magnesium diboride wire

Abstract: Abstract. The 4.2 K non-barrier transport Jc values of the powder-in-tube (PIT) in-situ MgB2 wires have been enhanced by cold high pressure densification (CHPD). With respect to the control wire, the 1.5 GPa pressure induced the Jc improvement of the wire at 4.2 K and 10 T by 25 %. The Jc enhancement induced by the CHPD may result from two aspects. First, the CHPD resulted in the reduction of the transverse MgB2 core area. Second, the grain connectivity of the PIT in-situ MgB2 wire was improved by the CHPD, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Figure 22 shows that the HIP process and an annealing temperature of 740 °C allow for a high n-value under low and medium magnetic fields in MgB2 wires with a mixture of boron grains. The results for sample O and the results in [46] (undoped MgB2 wires-CTFF method) indicate that the HIP process significantly increases the n-value above 7 T. Our research shows that the size of the boron grains significantly influences the critical parameters for the MgB2 material during the HIP process, as well as the Mg in the liquid state. Additionally, we proved that the HIP process and Mg in the liquid state improved the homogeneity of the MgB2 material structure, leading to improvements in the Jec and nvalue.…”
Section: Thermal Treatment At 740 • C Under High Isostatic Pressurementioning
confidence: 56%
See 1 more Smart Citation
“…Figure 22 shows that the HIP process and an annealing temperature of 740 °C allow for a high n-value under low and medium magnetic fields in MgB2 wires with a mixture of boron grains. The results for sample O and the results in [46] (undoped MgB2 wires-CTFF method) indicate that the HIP process significantly increases the n-value above 7 T. Our research shows that the size of the boron grains significantly influences the critical parameters for the MgB2 material during the HIP process, as well as the Mg in the liquid state. Additionally, we proved that the HIP process and Mg in the liquid state improved the homogeneity of the MgB2 material structure, leading to improvements in the Jec and nvalue.…”
Section: Thermal Treatment At 740 • C Under High Isostatic Pressurementioning
confidence: 56%
“…The results in Figure 17 indicate that the n-value is dependent mainly on the density of unreacted material and less dependent on the grain size for the solid-state Mg synthesis reaction. The research presented by Wan et al [46] shows that 2% carbon-doped MgB 2 PIT wires with nanoboron grains and an Nb barrier after pressure treatment have an n-value of 50 at 7 T. We obtain an n-value of 50 at 6.5 T for undoped MgB 2 wires with boron mixture grains (1 µm and 0.25 nm) under high isostatic pressure annealing, indicating that our undoped MgB 2 wires have high n-values and J ec . Our research showed that the density of unreacted material during the Mg solid-state synthesis reaction significantly influences the critical parameters (T c , B irr , B c2 , J ec , and n-value).…”
Section: Thermal Treatment At 700 • C Under High Isostatic Pressurementioning
confidence: 99%
“…The CHPD-processed strands were P10 (1.0 GPa cold-pressing) and P15 (1.5 GPa cold-pressing). According to the previous results of our group, the CHPD technique increased the transport J C of the monofilamentary PIT in-situ MgB 2 strand from 3.0 × 10 4 A/cm 2 to 3.6 × 10 4 A/cm 2 at 4.2 K and 10 T due to decreased porosity [ 11 ] and AIMI-processed MgB 2 strands attained the 4.2 K, 10 T transport layer J C s of 1.0 ~ 1.5 × 10 5 A/cm 2 [ 13 16 ]. In this study, we compared the J CM∥ s and transverse connectivity of the CHPD- and AIMI-processed strands with those of the P00 strand at 4.2 K and 20 K. The relationship between porosity and transverse flux pinning force density F p∥ , which is J CM∥ × B , for the in-situ MgB 2 strands was also discussed.…”
Section: Introductionmentioning
confidence: 78%
“…As shown in Figure 2(b) J CM∥ s were independent on the aspect ratio S. Based on this result, we can know the values of J CM∥ s as well as J CT s are merely determined by the intrinsic properties of the in-situ MgB 2 strands. The MgB 2 macrostructure of the reacted PIT in-situ strand is characterized by elongated polycrystalline MgB 2 fibers and elongated pores partially separating the fibers [ 7 , 11 , and 18 ]. The J CT s and J CM∥ s can represent the longitudinal and transverse connectivity of the MgB 2 fibers, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation